Future etiologic research in occupational cancer. - Siemiatycki, J (1995)
Research focused on occupational exposure has been one of the cornerstones of epidemiological research into the etiology of cancer. It is appropriate to critically assess the contribution of this research effort and to assess the potential for making significant progress in the future in unraveling the etiology of cancer by studying the occupational environment. The study of the occupational environment has indeed been very fruitful. It is likely that there remain many more carcinogens to be discovered, but we have not deployed adequately sensitive study methods. The two major obstacles to quality research have been inadequate exposure assessment and insufficient sample sizes. Quality exposure assessment requires the participation of trained experts (industrial hygienists, chemists, etc.); it also requires an adequate information base on the exposures that occur in different workplaces. We need structures and career paths that facilitate the participation of exposure experts in epidemiological research. We need active large-scale industrial hygiene surveys to better characterize the U.S. workplace. This will be useful for epidemiological studies and for public health purposes. Community-based case-control studies will need to be much larger than they have been traditionally, with 1000 as a minimum number of cases and controls.